Project-Based Learning (PjBL) Model in E-Module as an Improvement of Critical Thinking in the Department of Cosmetology And Beauty - Rahmi Oktarina; Siska Miga Dewi (The Indonesian Journal of Computer Science, 2023)
The goal of this research is to enhance learning and critical thinking abilities of Cosmetology and Beauty students in e-commerce courses through the implementation of interactive e-commerce e modules. This study uses a quasi-experimental approach with control groups for the pretest and posttest. Data collection was carried out using instruments in the form of open questionnaires and tests. The study's data analysis method is quantitative descriptive analysis, differentiation power analysis using T Test and qualitative descriptive analysis. The independent sample t test findings describe a Sig (2 Tailed) greater in the experimental class compared to the control class, it can be inferred that there is a substantial difference between the two groups. The overall findings support the usage of the e-module in e-commerce courses because it has been shown to enhance critical thinking abilities and learning outcomes.